Identification of Herpes Simplex Virus Type 1 Latency-Associated Transcript Sequences That both Inhibit Apoptosis and Enhance the Spontaneous Reactivation Phenotype - Jin, Ling (American Society for Microbiology, 2003)
The herpes simplex virus type 1 (HSV-1) latency-associated transcript (LAT) gene is essential for the high spontaneous and induced reactivation phenotype of HSV-1 in the rabbit ocular model and for the high induced reactivation phenotype in the mouse ocular model. Recently we showed that LAT has an antiapoptosis function, and we hypothesized that LAT's ability to inhibit apoptosis played an important role in LAT's ability to enhance the reactivation phenotype. Expression of just the first 1.5 kb of the 8.3-kb LAT gene is sufficient for both inhibition of apoptosis in an in vitro transient-transfection assay and the high spontaneous reactivation phenotype in vivo. Here we show the results of more complex mapping studies in which inhibition of apoptosis and the enhanced spontaneous reactivation phenotype also appear to be linked. The HSV-1 mutant virus dLAT371 has a high spontaneous reactivation phenotype in rabbits, suggesting that the LAT region deleted in this mutant (LAT nucleotides 76 to 447) is not required for this phenotype. The LAT3.3A viral mutant (which expresses LAT nucleotides 1 to 1499) also has a high spontaneous reactivation phenotype, suggesting that the region of LAT not expressed by this mutant (LAT nucleotide 1500 to the end of LAT) is also not required for this phenotype. Surprisingly, LAT2.9A, which is a combination of dLAT371 and LAT3.3A (i.e., it expresses LAT nucleotides 1 to 76 and 447 to 1499), has a low spontaneous reactivation phenotype indistinguishable from that of LAT null mutants. We report here that consistent with the low spontaneous reactivation phenotype of LAT2.9A, a plasmid expressing the identical LAT RNA did not inhibit caspase 9-induced apoptosis. In contrast, plasmids containing the same deletion but able to transcribe up to or past LAT nucleotide 2850 (rather than just up to LAT nucleotide 1499) inhibited caspase 9-induced apoptosis, consistent with the high spontaneous reactivation phenotype of dLAT371. Thus, LAT2.9A may have a low spontaneous reactivation phenotype because the LAT RNA that is made cannot block apoptosis, and dLAT371 apparently has a high spontaneous reactivation phenotype because the LAT RNA made has significant antiapoptosis activity. Furthermore, LAT appeared to have at least two regions capable of interfering with caspase 9-induced apoptosis. One region partially overlaps LAT nucleotides 76 to 447. The second region is partially (or completely) downstream of LAT nucleotide 1499.